Spaceborne Measurements of Formic and Acetic Acids: A Global View of the Regional Sources. Issue 4 (14th February 2020) - Franco, B.; Clarisse, L.; Stavrakou, T.; Müller, J.‐F.; Taraborrelli, D.; Hadji‐Lazaro, J.; Hannigan, J. W.; Hase, F.; Hurtmans, D.; Jones, N.; Lutsch, E.; Mahieu, E.; et al.
Abstract: Formic (HCOOH) and acetic acids ( CH 3 COOH) are the most abundant carboxylic acids in the Earth's atmosphere and key compounds to aqueous‐phase chemistry. Here we present the first distributions of CH 3 COOH retrieved from the 2007–2018 satellite observations of the nadir‐looking infrared atmospheric sounding interferometer (IASI), using a neural network‐based retrieval approach. A joint analysis with the IASI HCOOH product reveals that the two species exhibit similar distributions, seasonality, and atmospheric burden, pointing to major common sources. We show that their abundance is highly correlated to isoprene and monoterpenes emissions, as well as to biomass burning. Over Africa, evidence is provided that residual smoldering combustion might be a major driver of the HCOOH and CH 3 COOH seasonality. Earlier seasonal enhancement of HCOOH at Northern Hemisphere middle and high latitudes and late seasonal secondary peaks of CH 3 COOH in the tropics suggest that sources and production pathways specific to each species are also at play. Key Points: First atmospheric distributions of acetic acid are obtained from IASI/Metop observations In emission regions, formic and acetic acids highly correlate with each other and with biogenic hydrocarbon emissions and biomass burning Residual smoldering combustion appears to be a major driver of the formic and acetic acids seasonality in Africa